2018
DOI: 10.4193/rhin17.067
|View full text |Cite
|
Sign up to set email alerts
|

Lateral lamella of the cribriform plate, a keystone landmark: proposal for a novel classification system

Abstract: This angle classification is based on the theoretical risk of iatrogenic injuries, but it could be helpful also in clinical practice by providing indirect information on the thickness of the anterior skull base. As the angle decreases, in fact, the portion of the anterior skull base composed by the LLCP, increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
68
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(88 citation statements)
references
References 20 publications
16
68
3
1
Order By: Relevance
“…Table 4. Distribution of Gera 9 and TMS (Thailand-Malaysia-Singapore) classifications. Gera 9 and TMS classifications have no significant correlation (p = 0.804).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4. Distribution of Gera 9 and TMS (Thailand-Malaysia-Singapore) classifications. Gera 9 and TMS classifications have no significant correlation (p = 0.804).…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of Gera 9 and TMS (Thailand-Malaysia-Singapore) classifications. Gera 9 and TMS classifications have no significant correlation (p = 0.804). * Gera (Class I, low risk: the angle >80 degrees, Class II, medium risk: the angle ranged from 45 to 80 degrees, Class III, high risk: the angle <45 degrees).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical implication of deeper olfactory fossa and longer lateral lamella is clear. Lateral lamella of cribriform plate is the thinnest part of the skull base, which is known to be a common site of injury during sphenoethmoidectomy . The thickness of the lateral lamella, the most vulnerable part of the skull base, was reported to be only 0.05 mm .…”
Section: Discussionmentioning
confidence: 99%
“…Beside the length of the lateral lamella, the angle may also implicate that it might in part determine the association of lateral lamella with cribriform plate and fovea ethmoidalis. In a proposal based on the angle of the lateral lamella, Gera et al reported that the decreased angle of the lateral lamella was related to increased length. Thus, lateral lamellas with lower angles might be associated with a higher risk of iatrogenic injury.…”
Section: Discussionmentioning
confidence: 99%